MICROBIAL PATTERN OF DIABETIC FOOT ULCER PATIENT IN JEMURSARI ISLAMIC HOSPITAL SURABAYA PERIOD 2012-2016 - Adyan Donastin; Aisyah Aisyah (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2019)
Diabetic foot ulcers (DFU) are complications in people with diabetes mellitus (DM) in the form of wounds or tissue damage resulting in vascular insufficiency and or neuropathy that can develop into an infection. Early detection of germs of diabetic foot ulcers may be used as a recommendation of empirical therapy before the definitive treatment based on culture results and appropriate antibiotics treatment, which may reduce hospitalization time and amputation events. According to Riskesdas in 2013, state that the number of antibiotic used without prescriptions in Indonesia about 86.1%. The study aims to retrospectively analyze the bacterial culture and drug susceptibility test results for patients with diabetic foot ulcers (DFU) in Jemursari Islamic Hospital Surabaya during 2012–2016 to help clinicians choose a more appropriate empirical antibiotic treatment for DFU. This study used cross–sectional designed with retrospective approaches, which analyzed descriptively and samples were taken by the total sampling of 11 samples. This research was conducted at Islamic Hospital of Jemursari Surabaya in May–September 2017 by using medical record data which are outpatient and inpatients who treatment at Jemursari Islamic Hospital. The result was found 6 types of bacteria consisting of Staphylococcus aureus (18%), Staphylococcus non–haemolytic (18%), Klebsiella pneumonia (27%), Enterobacter aerogenes (18%), Burkholderia cepacia (9%), Escheria coli (9%). The most sensitive antibiotics in the Gram–positive bacteria in this study are Amikacin, Teicoplanin and Oxacillin and the most resistant to Amoxicillin and Ampicillin whereas the most sensitive antibiotics in the Gram–negative bacteria in this study were Meropenem and the most resistant to Ciprofloxacin and Trimethroprim–sulfamethoxazole.